About Literature, Dystopia and José Saramago: A conversation with Pilar Del Río - Araújo, Wagner Rodrigues (Revista Criação & Crítica, 2020)
In this unprecedented interview with the journalist Pilar del Río, also translator and writer, several questions are addressed: reflections pass through literature, memories, life projects, self-assertion, dystopias, José Saramago, Ignácio de Loyola Brandão, Fernando Pessoa, Miguel de Cervantes and other authors, Journalism, pandemic and Humanities. In this conversation, held in the midst of the crisis generated by Covid-19, she makes considerations about her relationship with José Saramago, the possibility that the pandemic is a new blindness, and even if the Portuguese writer would have foreseen this present dystopia. Focusing on the Humanities in general, the interview covers several important themes, such as dystopia, the role of literature and Saramago's writing process, the place of memories, life projects, the search for self-affirmation, reaching also other writers, such as Fernando Pessoa and Miguel de Cervantes.